Application of the Business Judgment Rule Doctrine to ESG Investment Decisions - Ogan Muhammad; Anggara Akbar Hasibuan (CV Edujavare Publishing, 2026)
The implementation of Environmental, Social, and Governance (ESG) investments often causes short-term profitability declines in corporations. This normative-juridical research aims to analyze directors' legal protection against such financial risks through the Business Judgment Rule (BJR) doctrine. The findings conclude that BJR excludes directors' personal liability provided the decision meets key procedural parameters: good faith, absence of conflict of interest, informed decision-making, and proper purpose. Short-term profit decline is reconstructed as a legitimate business risk for corporate longevity rather than managerial negligence, provided it is free from greenwashing